Small And Medium Entrepreneurs : Issues & Challenges - Jyothi, P (Journal of Commerce and Trade, 2009)
In some countries, there are certain objective standards, which classify the units as micro, small or medium enterprises depending on the number of employees. In some other countries, annual turnover of the company determines the size of an enterprise. The concept of size is also a relative phenomenon with reference to the local economies, since a large company in a small country could possibly be considered as a small company in a larger country. In the Indian context, primarily the concept of Small? Scale Industry (SSI) has been in vogue and the medium enterprise definition is of more recent origin. An SSI is defined on the basis of limit of historical value of investment in plant & machinery, which at present is upto Rs.10 million.